Kerapatan Clathria reinwardti dan Spheciospongia inconstans di Reef Flat Pulau Barranglompo, Kepulauan Spermonde, Makassar - Abdul Haris; Widyastuti Umar; Reski Adiguna; Andi Muh. Agung Pratama (Jurnal Kelautan Tropis, 2021)
This study aims to determine the density of the sponges Clathria reinwardti and Spheciospongia inconstans in the reef flat of Barranglompo Island, Spermonde Archipelago, Makassar. The method used is belt transect using a roll meter as a reference for distance. The starting point of the roll meter ± 50 m from the shoreline is drawn perpendicularly to the end of the reef reef by 3 transects with a distance of ± 50m between the roll meters. At each 25m interval the observations were made using a belt transect size of 15m × 5m as the limit of the observation. In each quadrant transect, were done first is documenting of each sponge then count the number of species present in each quadrant. The results showed that the density of Clathria reinwardti at stations I and II were 0.13 and 0.14 m-2 respectively and were not significantly different, while those at stations III and IV were 0.25 and 0.31 m-2 respectively and not significantly different. Station I and II are significantly different from stations III and IV. The density of Spheciospongia inconstans at station I 0.02 m-2, station II 0.14 m-2, station III 0.67 m-2, and station IV 0.44 m-2. The sponge density of S. inconstans between stations was significantly different. The density of C. reinwardti at stations III and IV was higher and significantly different than stations I and II, while the highest density of S. inconstans was found at station III followed by station IV, station II, and station 1, and was significantly different among the four stations.  Penelitian ini bertujuan untuk mengetahui kerapatan spons Clathria reinwardti dan Spheciospongia inconstans di reef flat Pulau Barranglompo, Kepulauan Spermonde, Kota Makassar. Metode yang digunakan adalah belt transect dengan menggunakan roll meter sebagai acuan jarak. Titik awal roll meter ±50 m dari garis pantai secara tegak lurus ditarik sampai batas akhir reef reef sebanyak 3 transek dengan jarak ±50m antar roll meter. Pada setiap interval 25m pengamatan dilakukan menggunakan belt transect ukuran 15m × 5m sebagai batasan pengamatan. Pada setiap transek kuadran, pertama-tama yang dilakukan adalah mengambil gambar setiap spons kemudian menghitung jumlah jenis yang terdapat pada setiap kuadran. Hasil penelitian, kerapatan spons Clathria reinwardti di stasiun I dan II masing-masing 0.13 dan 0.14 m-2 dan tidak berbeda nyata, sedangkan di stasiun III dan IV masing-masing 0.25 dan 0.31 m-2 dan tidak berbeda nyata. Stasiun I dan II berbeda nyata dengan stasiun III dan IV. Kerapatan spons Spheciospongia inconstans  pada stasiun I 0.02 m-2, stasiun II 0.14 m-2, stasiun III 0.67 m-2, dan stasiun IV 0.44 m-2. Kerapatan spons Spheciospongia inconstans antar stasiun berbeda nyata. Kerapatan Clathria reinwardti pada stasiun III dan IV lebih tinggi dan berbeda nyata daripada stasiun I dan II, sedangkan kerapatan Spheciospongia inconstans tertinggi didapatkan pada stasiun III disusul kemudian stasiun IV, stasiun II, dan stasiun 1, serta berbeda nyata di antara keempat stasiun tersebut.